Preconditioning for a Phase-Field Model with Application to Morphology Evolution in Organic Semiconductors (Communications in Computational Physics, 2023)
The Cahn–Hilliard equations are a versatile model for describing theevolution of complex morphologies. In this paper we present a computationalpipeline for the numerical solution of a ternary phase-field model for describingthe nanomorphology of donor–acceptor semiconductor blends used in organicphotovoltaic devices. The model consists of two coupled fourth-order partialdifferential equations that are discretized using a finite element approach. In order tosolve the resulting large-scale linear systems efficiently, we propose a preconditioningstrategy that is based on efficient approximations of the Schur-complement of a saddlepoint system. We show that this approach performs robustly with respect to variationsin the discretization parameters. Finally, we outline that the computed morphologiescan be used for the computation of charge generation, recombination, and transport inorganic solar cells.
Keywords: Preconditioning; phase–field models; organic solar cells; Cahn–Hilliard; finite element analysis.